Magneto-Optical Nanostructures for Viral Sensing - Sabine Szunerits; Tamazouzt Nait Saada; Dalila Meziane; Rabah Boukherroub (Nanomaterials, 2020)
The eradication of viral infections is an ongoing challenge in the medical field, as currently evidenced with the newly emerged Coronavirus disease 2019 (COVID-19) associated with severe respiratory distress. As treatments are often not available, early detection of an eventual infection and its level becomes of outmost importance. Nanomaterials and nanotechnological approaches are increasingly used in the field of viral sensing to address issues related to signal-to-noise ratio, limiting the sensitivity of the sensor. Superparamagnetic nanoparticles (MPs) present one of the most exciting prospects for magnetic bead-based viral aggregation assays and their integration into different biosensing strategies as they can be easily separated from a complex matrix containing the virus through the application of an external magnetic field. Despite the enormous potential of MPs as capture/pre-concentrating elements, they are not ideal with regard of being active elements in sensing applications as they are not the sensor element itself. Even though engineering of magneto-plasmonic nanostructures as promising hybrid materials directly applicable for sensing due to their plasmonic properties are often used in sensing, to our surprise, the literature of magneto-plasmonic nanostructures for viral sensing is limited to some examples. Considering the wide interest this topic is evoking at present, the different approaches will be discussed in more detail and put into wider perspectives for sensing of viral disease markers.